Somatic mTOR mutation in clonally expanded T lymphocytes associated with chronic graft versus host disease - Daehong Kim; Giljun Park; Jani Huuhtanen; Sofie Lundgren; Rajiv K. Khajuria; Ana M. Hurtado; Cecilia Muñoz-Calleja; Laura Cardeñoso; Valle Gómez-García de Soria; Tzu Hua Chen-Liang; Samuli Eldfors; Pekka Ellonen; et al. (Nature Research, 2022)
Graft versus host disease (GvHD) is the main complication of allogeneic hematopoietic stem cell transplantation (HSCT). Here we report studies of a patient with chronic GvHD (cGvHD) carrying persistent CD4+ T cell clonal expansion harboring somatic mTOR, NFKB2, and TLR2 mutations. In the screening cohort (n = 134), we detect the mTOR P2229R kinase domain mutation in two additional cGvHD patients, but not in healthy or HSCT patients without cGvHD. Functional analyses of the mTOR mutation indicate a gain-of-function alteration and activation of both mTORC1 and mTORC2 signaling pathways, leading to increased cell proliferation and decreased apoptosis. Single-cell RNA sequencing and real-time impedance measurements support increased cytotoxicity of mutated CD4+ T cells. High throughput drug-sensitivity testing suggests that mutations induce resistance to mTOR inhibitors, but increase sensitivity for HSP90 inhibitors. Our findings imply that somatic mutations may contribute to aberrant T cell proliferations and persistent immune activation in cGvHD, thereby paving the way for targeted therapies.